2020
DOI: 10.3892/or.2020.7461
|View full text |Cite
|
Sign up to set email alerts
|

DNA aneuploidy and tissue architecture in oral potentially malignant disorders with epithelial dysplasia assessed by a 10 locus FISH panel

Abstract: Subjectivity in oral dysplasia grading has prompted evaluation of molecular-based tests to predict malignant transformation. Aneuploidy detected by DNA image-based cytometry (ICM) is currently the best predictor but fails to detect certain high risk lesions. A novel multiplex fluorescence in situ hybridization (FISH) panel was used to explore possible explanations by detecting aneuploidy at the single cell level. FISH was compared to reference standard DNA ICM in 19 oral lesions with epithelial dysplasia and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…In line with that, in silico analyses of transcriptome data suggest that in some cases the premalignant lesions and the carcinomas are not clonally related to each other 47 . Furthermore, the results of a recent study using a FISH panel in oral epithelial dysplasia reinforce that dysplasia progression to OSCC can occur through neutral clonal evolution (ie randomly), instead of through non‐random selection 22 . However, more studies are necessary to exclude the possibility of non‐random selection of genetic alterations in OL progression.…”
Section: Gene Mutationsmentioning
confidence: 57%
See 4 more Smart Citations
“…In line with that, in silico analyses of transcriptome data suggest that in some cases the premalignant lesions and the carcinomas are not clonally related to each other 47 . Furthermore, the results of a recent study using a FISH panel in oral epithelial dysplasia reinforce that dysplasia progression to OSCC can occur through neutral clonal evolution (ie randomly), instead of through non‐random selection 22 . However, more studies are necessary to exclude the possibility of non‐random selection of genetic alterations in OL progression.…”
Section: Gene Mutationsmentioning
confidence: 57%
“…Interestingly, aneuploid cells formed a minority cell population in all cases and were shown to be interspersed with normal diploid cells in the oral dysplastic epithelium 22 . Notably, the authors also observed agreement in aneuploidy results by the FISH panel and image‐based cytometry in 17 of 19 samples 22 …”
Section: Dna Ploidymentioning
confidence: 58%
See 3 more Smart Citations